Porous CoP nanosheet arrays grown on nickel foam as an excellent and stable catalyst for hydrogen evolution reaction. (2nd November 2017) - Guo, Pan; Wu, Yu-Xuan; Lau, Woon-Ming; Liu, Hao; Liu, Li-Min
Abstract: Three dimensional porous CoP nanosheet arrays grown on nickel foam composite were designed and constructed through a combination of electrodeposition and phosphatization. Nanosheet arrays of cobalt (II) hydroxide were firstly formed on nickel foam via electrodeposition which is further phosphatized to form defect-rich porous CoP nanosheets. The as-prepared CoP nanosheets exhibit high activity as a catalyst for the hydrogen evolution reaction, and the overpotentials of generating a current density of 10 mA cm −2 are 79.5 mV and 86.6 mV in acidic and basic electrolytes, respectively. In addition, the as-prepared CoP nanosheet catalyst shows excellent stability in acidic electrolyte, and no obvious degradation was observed at 10 mA cm −2 for 50 h. The high activity is attributed to the unique three dimensional structure of the material as well as the metalloid characteristics of CoP. Highlights: 3D binder-free precursor was prepared by electrodeposition. 3D binder-free CoP nanosheet arrays was prepared by phosphatization. The CoP@NF exhibits high activity and stability towards HER in acidic and basic electrolyte.